2015
DOI: 10.1504/ijiscm.2015.075633
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel model of information system success in the user department: integrating job performance theory and field theory

Abstract: This study adapts from job performance theory and field theory, a multilevel model to identify and validate the antecedents and their effects on information system (IS) success in the user department. The model is validated by using hierarchical linear modelling (HLM) method with survey data of 283 user managers and 42 top managers collected from 42 manufacturing companies in China that were utilising ERP systems. The results reveal that top management support and user manager's knowledge and attitude all sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Although user satisfaction is widely acknowledged as one of the surrogate measures of information system success (Bailey and Pearson, 1983; Raymond, 1987; Wang and Liao, 2007; Petter et al , 2013; Hsu et al , 2015; Huang et al , 2015), in the AEC industry, what is BIM user satisfaction and in which way to measure the BIM user satisfaction are still underdiscovered. Therefore, the purpose of this study is to introduce the necessity and feasibility of BIM user satisfaction research and define what the BIM user satisfaction is, and then to develop a quantitative method for the measurement of BIM user satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although user satisfaction is widely acknowledged as one of the surrogate measures of information system success (Bailey and Pearson, 1983; Raymond, 1987; Wang and Liao, 2007; Petter et al , 2013; Hsu et al , 2015; Huang et al , 2015), in the AEC industry, what is BIM user satisfaction and in which way to measure the BIM user satisfaction are still underdiscovered. Therefore, the purpose of this study is to introduce the necessity and feasibility of BIM user satisfaction research and define what the BIM user satisfaction is, and then to develop a quantitative method for the measurement of BIM user satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a firm with KBDC would be amenable to change and can increase performance even in the SC disruption situation. Prior research revealed that top management's investment in providing managers with training experiences to enhance their knowledge could not influence organizational performance (Huang et al, 2015). In this vein, knowledge acquisition in organizations does not depend on financial investment.…”
Section: Ijopm 435mentioning
confidence: 99%